Nonlinear dynamic pulse buckling of imperfect laminated composite plate with delamination. (1st August 2020) - Mondal, Susmita; Ramachandra, L.S.
Abstract: The nonlinear dynamic pulse buckling of imperfect composite plate with embedded delamination is investigated numerically in this article. The dynamic buckling load is computed using Tsai-Wu quadratic interaction criterion. The laminated composite plate is modeled using layerwise theory with jump discontinuities in the form of heaviside step function to represent delamination at layer interfaces. The B-spline function is used as an interpolation function in finite element to analyze the plate subjected to unidirectional in-plane compressive pulse loading. The effect of type of pulse loading i.e., sinusoidal, exponential and rectangular, and plate boundary condition on the shock spectrum is explored. Response of delaminated plates is also computed for various delamination percentages at different layer interfaces. Sublaminates open up at the zone of delamination around peak displacement. Moreover, the same percentage of delamination at outer interface results in higher relative displacement of sublaminates compared to the delamination at inner interfaces. Dynamic load factor (DLF) is computed for different percentages of delaminations at middle interface.